Sistem Informasi Keuangan Pada Gereja GKI Efrata Kayu Batu Berbasis Website - Dalton, Timothy; Hasan, Patmawati; Tatuhey, Emy Lenora (JATISI, 2024)
In the era of information technology advancement, organization financial management, including churches, requires an efficient and transparent financial information system (FIS). GKI Efrata Kayu Batu Church still uses a manual financial management system that has various problems, such as administrative problems, lack of financial transparency, and slow financial reporting process.This study aims to build a website-based FIS at GKI Efrata Kayu Batu Church that can overcome these problems. The FIS that was built has features for financial data management, financial reporting, cash flow tracking, financial data analysis, and the creation of special financial reports.This study used the waterfall method with observation, interview, and literature study as data collection techniques. The analysis model used was object-oriented analysis using UML and coding using the C# programming language and database management using MySQL. Blackbox testing was used to test the functionality of the system.The results of the study showed that the website-based FIS that was built can overcome the financial management problems at GKI Efrata Kayu Batu Church. This FIS can help church financial managers to manage financial data more efficiently and effectively, generate complete and informative financial reports, track cash flow in real time, analyze financial data to gain useful insights, and create special financial reports according to the type of cash. Keywords— Financial information system, Church, Financial management